Distributions of vascular plants in the Czech Republic. Part 7 - Kaplan, Zdeněk; Danihelka, Jiří; Chrtek, Jindřich; Prančl, Jan; Ducháček, Michal; Ekrt, Libor; Kirschner, Jan; Brabec, J.; Zázvorka, Jiří; Trávníček, Bohumil; Dřevojan, Pavel; Šumberová, Kateřina; et al. (Preslia)
The seventh part of the series on the distributions of vascular plants in the Czech Republic includes grid maps of 104 taxa in the genera Anthriscus, Callitriche, Cochlearia, Dittrichia, Egeria, Elodea, Elymus, Epilobium, Gentianella, Gnaphalium, Gymnocarpium, Hordeum, Hydrocharis, Limonium, Najas, Phleum, Phragmites, Polypodium, Pseudognaphalium, Rubus, Sedum, Senecio, Setaria, Stratiotes, Trichomanes and Woodsia. These maps were produced by taxonomic experts based on examined herbarium specimens, literature and field records. Many of the studied native species are on the national Red List. The genus most affected by decline in abundance is Gentianella, which includes six taxa extirpated from this country and six taxa critically threatened. Another group with a high proportion of endangered species comprises aquatic and wetland plants, which are represented by Callitriche hermaphroditica, Hydrocharis morsus-ranae, Najas minor, Pseudognaphalium luteoalbum and Stratiotes aloides. Other ecologically specialized groups include mainly montane wetland plants (Epilobium anagallidifolium, E. nutans and Rubus chamaemorus) and plants of rocky habitats (Polypodium interjectum, Trichomanes speciosum and Woodsia ilvensis). The previously rare Woodsia alpina has been extirpated from this country. Alien species mapped in this paper include both archaeophytes and neophytes, mainly from the genera Anthriscus, Cochlearia, Elodea, Epilobium, Hordeum and Phleum. Cochlearia danica, Dittrichia graveolens and Limonium gmelinii have recently colonized habitats along the roads treated by de-icing salt. Senecio inaequidens has also spread mainly along motorways. Epilobium adenocaulon is another successful neophyte; it is now widespread throughout this country and the most successful hybrid parent within the genus. Neophyte aquatics are represented by Egeria densa, Elodea canadensis and E. nuttallii. Spatial distributions and often also temporal dynamics of individual taxa are shown in maps and documented by records included in the ...